The Diagnostic Performance of Cardiovascular System and Evaluation of Hemodynamic Parameters Based on Heart Cycle Phase Analysis - Rudenko, Mikhail; Voronova, Olga; Zernov, Vladimir; Mamberger, Konstantin; Makedonsky, Dmitry; Rudenko, Sergey; Fedossov, Yuri; Duyzhikov, Alexander; Orlov, Anatoly; Sobin, Sergey (IntechOpen, 2012)
None